THE INFLUENCE OF COMPUTER ASSISTED LANGUAGE LEARNING ON STUDENTS’ LISTENING SKILLS. - Rizki Nuraida; Hilma Suryani (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2023)
This study was conducted to determine the influence of computer-assisted language learning on students' listening skills. This research uses descriptive quantitative method in the form of a survey. This method is considered as the right approach for this type of research. Data was collected by distributing it to each class to all twelfth grade in SMAN 4 Batanghari. This study explores students' perceptions that come from students' experiences during the learning process. The results of this study are presented descriptively to reveal students' perceptions comprehensively. This study has a positive influence on computer-assisted language learning by obtaining a Likert scale score which is included in the high category, named 63.70%. it can be concluded that CALL technology can be said to be goood enough to continue to be used in the learning system